Impact of Residency Area on Dental Caries and Nutritional Status among 10 Years Old Children in Al-Hillah City, Iraq - Sarah Y. AL Khafaji1, Nadia Aftan Al Rawi1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The dental caries are still the most common oral disease affecting children through the world especially in developing countries as in Iraq; however, these are not life threating human disease.This study was conducted to assess dental caries experience and the nutritional status among 10 years old primary school children in urban and rural area in Al-Hillah city.Eight hundred ninety one (891) students, 10 years old, selected randomly from different primary school, in urban and rural area in Al-Hillah city. Oral examination of dental caries was done according to the criteria described by WHO in 1987. Nutritional status was assessed according to body mass index (BMI), then followed the criteria of Centers for Disease Control and Prevention growth chart (CDC).A high percentage of total samples were affected with dental caries and significantly higher in urban areas than rural areas. The majority of children had normal weight and the lowest percentage had underweightThis study revealed that a higher prevalence of dental caries experience was recorded, in children of urban than children of rural areas. Therefore, there is need for an improving public and school preventive programs, and encouraged to orient health knowledge in a positive direction.